COMPARATIVE FUNCTION-STRUCTURAL ANALYSIS OF ANTIPLATELET AND ANTIRADICAL ACTIVITIES OF FLAVONOID PHYTOCHEMICALS - Chunmei Guo; Shuqing Liu; Yimeng Guo; Yuling Yin; Jintao Lin; Xin Chen…; Ming-Zhong Sun (Journal of Animal and Plant Sciences, 2014)
The antiplatelet and antiradical activities of 8 dietary flavonoid phytochemicals were investigated and compared. Quercetin, rutin, isoquercitrin, hesperetin, naringenin, hesperidin, naringin and icariin inhibited ADP-induced rat platelet aggregation by 68.33±2.43%, 55.34±2.09%, 52.27± 4.65%, 50.80±7.03%, 33.07±2.09%, 31.28±4.65%, 22.91±1.68% and 20.94±3.20%, respectively. Only quercetin, rutin and isoquercitrin showed clear scavenging HO· radical activity. Function-structure analysis indicated 1) flavonoids with more free phenolic hydroxyl groups showed relative higher antiplatelet and antiradical activities; 2) substitution of 7-OH of A ring affected antiplatelet capacities of flavanones apparently; 3) free 3-OH of C ring was important for both the antiplatelet and antiradical activities of flavonol (quercetin) and flavones (rutin, isoquercitrin); 4) C ring C2-C3 double bond and B ring 3’-4’orthodihydroxy might be important for its antiradical function. This study provides certain clues for evaluating a favorable dietary flavonoid drugs from our foods in prevention and treatment of related diseases associated with platelet aggregation and hyroxyl radical oxidation.
Keywords: Flavonoids; Antiplatelet; Antiradical; Function; Structure